Chikungunya virus modulates the miRNA expression patterns in human synovial fibroblasts. Issue 2 (10th September 2019) - Agrawal, Meghna; Pandey, Neha; Rastogi, Meghana; Dogra, Smriti; Singh, Sunit K.
Abstract: Chikungunya virus (CHIKV) is an alphavirus transmitted by mosquitoes. CHIKV infection leads to polyarthritis and polyarthralgia among patients. The synovial fibroblasts are the primary target for CHIKV. The microRNAs (miRNAs) are the small endogenous noncoding RNAs which posttranscriptionally regulate the expression of genes by binding to their target messenger RNAs (mRNAs) through their 3′‐untranslated regions. The miRNAs are the key regulators for various pathological processes including viral infection, cancer, cardiovascular disease, and neurodegeneration. This study was designed to dissect out the roles of miRNAs during CHIKV (Ross Strain E1: A226V) infection in primary human synovial fibroblasts. The miRNA microarray profiling was performed on the primary human synovial fibroblasts infected by CHIKV. The gene target prediction analysis, enrichment, and network analysis were performed by various bioinformatics analyses. The subset of 26 differentially expressed microRNAs (DEMs) were identified through microarray profiling and were further screened for gene predictions, Gene Ontology, pathway enrichment, and miRNA‐mRNA network using various bioinformatics tools. The bioinformatics analysis indicates the role of DEMs by suppressing the immune response which may contribute to CHIKV persistence in human primary synovial fibroblasts. Our study provides the plausible roles of DEMs, miRNAs, and mRNA interactions and pathways involved in the molecular pathogenesis of CHIKV. Highlight: Chikungunya Virus is an Alphavirus transmitted by mosquitoes. Chikungunya Virus perturbs the expression of microRNAs in human synovial fibroblasts. Chikungunya Virus modulates the expression of various genes involved in Inflammation and cell death through microRNAs.